Analysis of Health Problem Factors with the Presence of Aedes Albopictus Mosquito Larvae in Water Reservoirs - Ervan, Ervan; Musaidah, Musaidah; Mainassy, Meillisa Carlen; Pannyiwi, Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Aedes aegypti is a mosquito that can act as a vector for dengue fever. Aedes aegypti prefers stagnant water in a container, not stagnant water on the ground. Potential breeding places are water reservoirs used for daily needs such as drums, bathtubs, toilet bowls, jars, buckets and others. The purpose of this study was to determine what factors are related to the presence of aedes aegypti mosquito larvae in the Nusa Harapan Permai complex. This research method is explanatory research with a cross-sectional study with a random sampling technique, so that the number of samples is obtained. The instruments in this study were questionnaires and checklists using univariate and bivariate data analysis. From the research results, it was found that there is a relationship between the implementation of mosquito nest eradication (PSN) , there is a relationship between TPA, there is a relationship between the existence of solid waste and the existence of larvae and there is no relationship between the frequency of mosquito larvae visits and the existence of larvae. In conclusion, there is a relationship between the implementation of mosquito nest eradication (PSN), TPA, and the existence of solid waste with the presence of larvae, and there is no relationship between the frequency of mosquito larvae visits and the presence of larvae.